Immoral desires: media violence in news about lesbophobia in private spaces for public use - Soares Rodrigues, Maria Clara (2026)
Introduction: This article focuses on the media violence faced by lesbian women in the Brazilian journalistic context. For this purpose, a Brazilian news portal with great national impact, G1, was selected, and from it, the journalistic representations of three cases of lesbophobic violence were studied. Main objective: To analyze the construction of news about lesbophobia in order to identify approaches, languages ​​and narrative strategies of the media. Method and technique: Qualitative research based on three news articles from the G1 Portal about cases of lesbophobia that occurred in 2021, 2022 and 2023. The material was analyzed using an adaptation of the methodological protocol for Journalistic Coverage Analysis. Results: The erasure of lesbianism was observed (which occurs not only in the narratives themselves, but also in the lack of coverage of the cases); the sensationalization of the violence and pain of the victims; the lack of contextualization of the systemic nature of lesbophobia; the restricted use of sources and the reinforcement of the «immoral» attribution to lesbianism and its affections. Conclusions: Understanding that the media coverage of the cases analyzed exposed the victims to media violence, it is concluded that, instead of informing and contributing to educating about lesbianities, G1 journalism has acted to produce and reinforce negative social imaginaries regarding lesbianism – such as those related to immorality.